Thermoplastic starch/beeswax blend: characterization on thermal mechanical and moisture absorption properties - Jumaidin, Ridhwan; Zakuan, Nur Diyana; Selamat, Mohd Zulkefli; Mohd Suan, Mohd Shahadan (Elsevier B.V., 2021)
Cassava starch has acquired many attentions owing to its ability to be developed as thermoplastic cassava starch (TPCS) where it can be obtained in low cost, making it to be one of alternatives to substitute petroleum-based plastic. An attempt was made to investigate the thermal, mechanical and moisture absorption properties of thermoplastic cassava starch blending with beeswax (TPCS-BW) fabricated using hot moulding compression method in the range of beeswax loading from 0, 2.5, 5 to 10 wt%. Addition of beeswax has significantly reduced tensile strength, elongation and flexural strength while improving tensile modulus and flexural modulus until 5 wt% beeswax. Incorporation of 10 wt% beeswax has successfully produced the lowest value of moisture absorption and water solubility among the bio-composite which might be attributed to the beeswax's hydrophobic properties in improving water barrier of the TPCS-BW bio-composite. Furthermore, the addition of beeswax resulted in the appearance of irregular and rough fractured surface. Meanwhile, fourier transform infrared (FT-IR) spectroscopy presented that incorporation of beeswax in the mixture has considerably improve hydrogen bonding of blends indicating good interaction between starch and beeswax. Hence, beeswax with an appropriate loading value able to improve the functional properties of TPCS-BW bio-composite.